Fault lines eaudiobook A novel. - Itami, Emily (2021)
SHORTLISTED FOR THE COSTA FIRST NOVEL AWARD ""What is the cost of a mother's desire?...Emily Itami explores this question with wit and poignancy."" — New York Times Book Review ""The perfect marriage of Sally Rooney and early Murakami."" — Kathy Wang, author of Impostor Syndrome Mizuki is a Japanese housewife. She has a hardworking husband, two adorable children, and a beautiful Tokyo apartment. It's everything a woman could want, yet sometimes she wonders whether she would rather throw herself off the high-rise balcony than spend another evening not talking to her husband and hanging up laundry. Then, one rainy night, she meets Kiyoshi, a successful restaurateur. In him, she rediscovers freedom, friendship, and the neon, electric pulse of the city she has always loved. But the further she falls into their relationship, the clearer it becomes that she is living two lives—and in the end, we can choose only one. Funny, provocative, and startlingly honest, Fault Lines is for anyone who has ever looked in the mirror and asked, who am I and how did I get here? A bittersweet love story and a piercing portrait of female identity, it introduces Emily Itami as a debut novelist with astounding resonance and wit.